Looking out for the National Interest: The Principles of the Council of Economic Advisers - Stiglitz, Joseph E. (American Economic Review, 1997)
The year 1996 marked the 50th anniversary of what has turned out to be an enormously successful institutional innovation: the Council of Economic Advisers (CEA). It was neither obvious nor inevitable that the CEA would enjoy the success it has had. Who would have thought that a group of academics, typically with little or no experience with politics or realpolitik, would not only survive in the rough-and-tumble of Washington, but also thrive and have some influence over policy? To be sure, the CEA's influence has fluctuated and has had to be established anew with each administration. But the durability of the institution, despite repeated reexaminations, is a testimony to the contribution that it has made in both Democratic and Republican administrations.